Intraparticle Mass Transfer Model of Ethylene Polymerization Catalyzed by Supported Metallocene - Huang, Kai; Xie, Ruijin (Asian Journal of Chemistry, 2012)
The slurry ethylene polymerization catalyzed with a silica-supported metallocene catalyst was simulated based on a modified multigrain model. The modified model combined with the intrinsic reaction investigation was used to analyze the catalyst fragmentation and the polyethylene intraparticle mass transfer. The model can also be used to calculate the monomer concentration and the evolution of the macroparticle size. Furthermore, the model can also be used to predict the changes of the particle porosity and the monomer concentration distribution. The results show that the intraparticle mass transfer resistance has great effect on the polymerization and the catalyst fragmentation will take place shell by shell from the surface to the center after 200 s of the polymerization time.